The rate of natural hybridization in common beans, in Patos de Minas, Minas Gerais - Pereira Filho, Israel Alexandre; Cavariani, Claudio (Pesquisa Agropecuaria Brasileira, 2014)
In order to evaluate the frequency of natural hybridization in common beans (Phaseolus vulgaris L.), two bean varieties were planted in Patos de Minas, MG, Brazil, in alternated rows, at two different seasons. In both rainy and dry seasons of the 1982/1983 agricultural year, the rate of 1% of hybridization was found. During the growth of cultivation, a great presence of thrips was observed, which were the most probable natural cross-pollination vectors.